2002
DOI: 10.1103/physrevlett.89.035003
|View full text |Cite
|
Sign up to set email alerts
|

High Energy DensityZ-Pinch Plasma Conditions with Picosecond Time Resolution

Abstract: Using an X-pinch configuration, we have determined that micropinches produced by exploding-wire z pinches can have densities approaching solid density and temperatures of 0.5-1.8 keV, depending upon the wire material used. These plasma parameters, determined from x-ray spectra recorded using an x-ray streak camera, vary drastically on time scales ranging from <10 to 100 ps. Computer simulations require radiation loss to reproduce the observed plasma implosion, suggesting that a radiative-collapse hypothesis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 15 publications
0
34
0
1
Order By: Relevance
“…The structure of the stagnated Zpinch has been studied with x-ray self-emission diagnostics, which can derive a temperature map of the pinch with a spatial resolution of 70-150 µm [3]. X-ray radiography was applied to X-pinches, a single wire and ablation and implosion stages in wire-array Z-pinches [6,15,16].…”
mentioning
confidence: 99%
“…The structure of the stagnated Zpinch has been studied with x-ray self-emission diagnostics, which can derive a temperature map of the pinch with a spatial resolution of 70-150 µm [3]. X-ray radiography was applied to X-pinches, a single wire and ablation and implosion stages in wire-array Z-pinches [6,15,16].…”
mentioning
confidence: 99%
“…This has led to their application as an x-ray (1-10 keV) backlighter by Pikuz et al (1997) and Shelkovenko et al (2001b) for diagnosing dense plasmas. Pikuz et al (2002) showed that these systems can be driven with currents as low as a few tens of kilo-amps, and are therefore a convenient and low-cost medium for the study of high energy density (>10 11 J/m 3 ) and radiation dominated plasmas. While previous research has focused on the formation of the hot-spot, more recently studies have also investigated the low density coronal plasma ablated from the wires by the drive current.…”
mentioning
confidence: 99%
“…[6][7][8] In the standard arrangement, the spectrum is formed on the Rowland circle in the meridional plane and spatial resolution is obtained by focusing in the saggital direction. 6,7 In the experiments described here the spherically bent mica crystal with R = 186 mm was positioned far from the pinch with good debris shielding.…”
Section: Experiments Arrangement and Resultsmentioning
confidence: 99%